Infectious laryngotracheitis: a review - H Hidalgo (Brazilian Journal of Poultry Science, 2003)
Infectious laryngotracheitis (ILT) herpesvirus continues to cause outbreaks of respiratory disease in chickens world-wide. Sporadic cases of ILT occur in all classes of birds, including hobby/show/game chickens, broilers, heavy breeders, and commercial laying hens. These epornitics of ILT tend to occur where there are large populations of naïve, unvaccinated birds, i.e., in concentrated areas of broiler production. ILT virus can be transmitted through (a) chickens with acute upper respiratory tract disease, (b) latently infected "carrier" fowls, and (c) fomites and contaminated persons. Chicken flocks which are endemic infected with ILT virus occur only in some regions of countries or even in particular multiple-age production farms. In these cases modified live vaccines are actually used, even though these biological products, as well as wild ILTV strains, can establish latent infections. In the case of heavy breeders and laying hens, which are typically vaccinated against ILT, sporadic cases are often related to errors in vaccine application and to biosecurity failures.